2018
DOI: 10.1038/s41389-018-0050-x
|View full text |Cite
|
Sign up to set email alerts
|

Dysregulation of the MiR-449b target TGFBI alters the TGFβ pathway to induce cisplatin resistance in nasopharyngeal carcinoma

Abstract: Despite the improvement in locoregional control of nasopharyngeal carcinoma (NPC), distant metastasis (DM), and chemoresistance persist as major causes of mortality. This study identified a novel role for miR-449b, an overexpressed gene in a validated four-miRNA signature for NPC DM, leading to chemoresistance via the direct targeting of transforming growth factor beta-induced (TGFBI). In vitro shRNA-mediated downregulation of TGFBI induced phosphorylation of PTEN and AKT, increasing cisplatin resistance. Conv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
45
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 38 publications
(51 citation statements)
references
References 66 publications
5
45
0
Order By: Relevance
“…TGFBI protein has been detected in most normal human tissues [229]. Although TGFBI is a downstream component of TGF-β signaling pathway, its expression is regulated not only by TGF-β, but also by other factors and mechanisms, such as autophagy [230], microRNAs [231], interleukin (IL)-1β [232], IL-4 [233], tumor necrosis factor α (TNFα) [232], cancerassociated fibroblasts (CAFs) [234], and high glucose concentrations [235,236]. TGFBI mediates cell adhesion, migration, proliferation, apoptosis, and angiogenesis through interaction with several ECM molecules (e.g.…”
Section: Transforming Growth Factor B Induced (Tgfbi) Protein and Brmentioning
confidence: 99%
“…TGFBI protein has been detected in most normal human tissues [229]. Although TGFBI is a downstream component of TGF-β signaling pathway, its expression is regulated not only by TGF-β, but also by other factors and mechanisms, such as autophagy [230], microRNAs [231], interleukin (IL)-1β [232], IL-4 [233], tumor necrosis factor α (TNFα) [232], cancerassociated fibroblasts (CAFs) [234], and high glucose concentrations [235,236]. TGFBI mediates cell adhesion, migration, proliferation, apoptosis, and angiogenesis through interaction with several ECM molecules (e.g.…”
Section: Transforming Growth Factor B Induced (Tgfbi) Protein and Brmentioning
confidence: 99%
“…First, the microarray analysis and validation of tissue samples and cell lines revealed that miR‐449b‐3p might be involved in the carcinogenesis and progression of NPC. Bissey P A et al confirmed that the dysregulation of miR‐449b alters the TGF‐β pathway to induce cisplatin resistance by targeting TGFBI in NPC . Moreover, chemoradiotherapy‐treated patients with NPC and high miR‐449b levels showed an inferior 5‐year overall survival to those of low‐miR‐449b‐expressing patients (72.8% vs 91.8%, P = .017).…”
Section: Discussionmentioning
confidence: 94%
“…We had previously demonstrated that miR-449b overexpression, another component of the validated prognostic DM signature [11], led to TGFBI mRNA degradation with subsequent TGFβ1 accumulation [12]. Given that TGFβ1 plays an important role in NPC progression [53,[63][64][65][66][67][68] and in the regulation of miRNAs, particularly miR-34a [52], we sought to measure TGFβ1 in these cell lines.…”
Section: Mir-34c Is Downregulated By Tgfβ1mentioning
confidence: 99%
“…Another component of the four-miRNA DM signature is miR-34c, which was only compared to other described [12]. NP69 and NP460 cell lines were generated by SW Tsao's group [55,56] and served as "normal" cells throughout this study.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation